State Selectivity in the Criminalization of Ideology in Indonesia: A Case Study of Communism: Selektivitas Negara dalam Kriminalisasi Ideologi di Indonesia: Studi Kasus Komunisme - Yoel Edward Hasugian; Daniel Naik Parulian Tampubolon; Mehaga Limar Ginting (Universitas Indo Global Mandiri, 2026)
Purpose : This study aims to analyze how the state constructs communism as an ideological threat in Indonesian politics through criminal law instruments and to assess the extent to which this construction reflects political selectivity in responding to ideologies deemed contrary to Pancasila. Design/methodology/approach : This research employs a qualitative-descriptive method with an interpretive-critical approach based on interpretive policy analysis. Data were collected through document studies of legal materials, academic literature, and policy documents, and analyzed using discourse analysis, framing, and process-tracing techniques to examine the relationship between discursive construction and legal formation. Findings : The findings reveal that the criminalization of communism is a historically institutionalized political-legal construction shaped by collective memory, state narratives, and power interests. The state consistently employs criminal law to frame communism as an existential threat, while other ideologies are addressed through more varied and non-penal approaches, indicating political selectivity that is not fully grounded in empirical threat assessment. Practical Implication : These findings highlight the need to reorient ideological criminalization policies by positioning criminal law as an ultimum remedium and promoting more proportional, evidence-based, and human rights–oriented approaches to prevent the abuse of power. Originality/value : This study contributes a novel perspective by integrating political law analysis, selective enforcement theory, and state ideology studies into a unified analytical framework, demonstrating that selectivity operates not only in law enforcement but also in norm construction and the production of ideological threats. Paper type : Research Paper